GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) survey III: South Galactic Pole data release. (6th April 2021) - Franzen, T. M. O.; Hurley-Walker, N.; White, S. V.; Hancock, P. J.; Seymour, N.; Kapińska, A. D.; Staveley-Smith, L.; Wayth, R. B.
Abstract: We present the South Galactic Pole (SGP) data release from the GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) survey. These data combine both years of GLEAM observations at 72–231 MHz conducted with the Murchison Widefield Array (MWA) and cover an area of 5 113 $deg^{2}$ centred on the SGP at $20^{h} 40^{m} < RA < 05^{h} 04^{m}$ and $-48^{°} < Dec < -2^{°} $ . At 216 MHz, the typical rms noise is ${≈}5$ mJy beam –1 and the angular resolution ${≈}2$ arcmin. The source catalogue contains a total of 108 851 components above $5σ$, of which 77% have measured spectral indices between 72 and 231 MHz. Improvements to the data reduction in this release include the use of the GLEAM Extragalactic catalogue as a sky model to calibrate the data, a more efficient and automated algorithm to deconvolve the snapshot images, and a more accurate primary beam model to correct the flux scale. This data release enables more sensitive large-scale studies of extragalactic source populations as well as spectral variability studies on a one-year timescale.